Rancangan Sistem Cari dan Temu Barang Hilang di Universitas Udayana Berbasis Web - Salsabila, Zerina Nur; Putra, I Gusti Ngurah Anom Cahyadi (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
Losing items is an event that has been experienced by all of us. At Udayana University itself, loss of goods is still a common problem that is often faced by students, lecturers, and staff. This of course can result in material loss and inconvenience for the owner of the goods. Currently at Udayana University to disseminate information on the announcement of lost items is still by means of social media only. To overcome this problem, a web-based lost and found system was designed called "Lost Goods Search and Find System at Udayana University". This system allows users to report lost items and share information on found items. Udayana's Lost and Found System is expected to help increase the chances of finding lost items and reduce material losses for the owner of the goods. This system can also help improve security and comfort at Udayana University.